(untitled) (Zaporizhzhia Historical Review, 2021)
On the basis of censuses of population, the author explains the particularities of russification and ukrainisation processes in Melitopol. The three indicators of official statistics are being analyzed. They repulse a number of representatives of the nationalities, Russian- and Ukrainian- language population, and persons, who recognized language of their own nationality. The analysis of the sources proves that contrary to the opinion – russification of Melitopol`s population was more intensive in independent Ukraine, than in imperial and soviet time.